ANALISIS PENGARUH TATA KELOLA PERUSAHAAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEI tahun 2016-2018) - Arlissa Rizky Audityani; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to examine the impact of corporate governance measured using transparency and disclosure index (TDI), and firm characteristics that are proxied using firm size, firm profitability, firm growth, and managerial ownership on dividend policy in Indonesia. The independent variable is corporate governance, firm size, firm profitability, firm growth and managerial ownership while the dependent variable is dividend policy. The data that was used in this research was secondary data from the financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 and selected by using purposive sampling method. A linear-multiple regression analysis was used to test the hypothesis of this study.The results showed that corporate governance, firm size, and managerial ownership not have significant effect to dividend. On the other hand, firm profitability has a positive and significant effect, while firm growth has a negative and significant effect on dividend policy.